99 A multi-dimensional approach towards implementing the effective use of remote electrocardiographic monitoring – evaluation of clinical correlation and patient experience. (6th June 2022) - Asad, Muhammad; Younas, Waqar; Kazi, Sayed Irfan; Alaguraja, Priyanth; Makan, Jayesh
Abstract : Background: Inappropriate use of telemetry results in the overuse of limited resources, disrupted provider workflow, higher costs of care, and false alarms with resultant alarm fatigue. Moreover, identifying a useful implementation blueprint is an important component of promoting its appropriate use. Telemetry can influence patient experience during their stay as potentially it can disturb sleep, contribute to delirium, and increase patient frustration and anxiety. We stipulate that even minor adjustments to monitoring practices can influence optimised patient care.We aimed to evaluate the co-existing standards of practice regarding use of telemetry across Shrewsbury and Telford Hospital NHS Trust (SaTH). We implemented a patient-centred approach towards quality improvement by incorporating record of patient experience as a tool to guide effective use of this limited resource across our district general hospital settings. Methods: Patients across two hospital sites were selected to conduct a prospective health service evaluation related to the use of telemetry. A likert scale survey was conducted to record patient perspective of telemetry monitoring including a section with an opportunity to provide feedback towards service improvement. The data of patients receiving telemetry was collected from December 2021 to February 2022.American Heart Association (AHA) consensus statement for remote electrocardiographic monitoring was utilized to evaluate the proposed indication for telemetry. However, the rating system helped group patients receiving telemetry monitoring as Class I (definitely indicated), Class II (maybe indicated), or Class III (not indicated). Clinical notes and electronic telemetry system was employed to record parameters including patient demographics; presenting complaint; class (I-III) of indication; whether an indication for telemetry was documented; the length of telemetry; and the details of any significant events that occurred during monitoring including escalation. Where possible, patients were asked to anonymously provide feedback via set questionnaire focusing on quality of care received by the patient.Results:Among the 30 patients who were included in our analysis, 7 were females and the average age in our cohort was found to be 72.8. In about 56% of the patients, there was no clear indication mentioned in the clinical notes regarding continuation/discontinuation of telemetry. Based on proposed indication, about 36.66% (11 patients out of which 2 were female) were identified to be at significant risk of an immediate life-threatening arrhythmia (Class I). Among this group, 2 patients were reported to have significant arrhythmia event necessitating treatment. Further analysis revealed that from our cohort, 46.66% (14 patients) had a Class II indication for their telemetry monitoring out of which only 2 patients had a significant event recorded. However, only 16.66% (5 patients) were found to meet the eligibility for Class III indications and none of them encountered a significant arrhythmia.From anonymously filled patient questionnaires, around two-third of the patients reported not being informed about the utility of telemetry and its predicted duration of stay. One-third of patients reported the device to be inconvenient, intrusive and heavy. Conclusions: To accomplish a sustainable improvement, a patient-centred approach should be exercised to help identify the gaps in quality of care delivered. Our analysis showed that significant number of patients received telemetry when it was not clinically indicated. The proposed interventions include adopting formal request process for telemetry, predicting its duration, use of patient education tools and exploring compatibility of telemetry device used. Larger scale studies are required to gain more insight into the appropriateness and impact of telemetry in a hospital setting. Conflict of Interest: None